Resilience of Ecotourism Activities to Climate Change, Case Study: Nyarai Tourism Destination, Padang Pariaman - Nofriya Nofriya; Ahmad Fadhly (Program Pascasarjana Universitas Sriwijaya, 2022)
Nature-based tourism is an activity that is vulnerable to this condition, so it is necessary to build the adaptive capacity of the tourism system. Nyarai ecotourism site is a nature-based activity and vulnerable to environmental degradation and threatened by climate change. This study aims to assess the resilience of the actively involved people in implementing ecotourism against climate change at the Nyarai tourist attraction. This study uses a quantitative analytical approach using a survey method to a specified sample of 117 tour guide populations. Primary data collection was done by interviewing through a questionnaire and analyzed descriptively. This research found the three lowest scores were on the criteria of economic resilience, namely statements about the existence of local projects in tourism activities (4.34), developing new tourism products and activities (4.41), and providing local products for tourists to buy (4.41). Nevertheless, economic, social, ecological, and governance resilience need to work together to increase tourism activities that lead to sustainable development and climate resilience.